2013
DOI: 10.1136/jnnp-2013-306095
|View full text |Cite
|
Sign up to set email alerts
|

The G1662S NaV1.8 mutation in small fibre neuropathy: impaired inactivation underlying DRG neuron hyperexcitability

Abstract: We report for the first time a mutation of NaV1.8 which impairs inactivation, in patients with painful I-SFN. Together with our earlier results, our observations indicate that an array of NaV1.8 mutations, which affect channel function in multiple ways, can contribute to the pathophysiology of painful peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 35 publications
(57 reference statements)
2
101
1
1
Order By: Relevance
“…Sodium channels Nav1.7, Nav1.8, and Nav1.9 are preferentially expressed in peripheral neurons. Gain-of-function mutations of human Nav1.7 and Nav1.8 channels have been associated with SFN (Faber et al 2012a, b;Han et al 2012Han et al , 2014Hoeijmakers et al 2012b;Huang et al 2013). More recently, seven mutations in Nav1.9 channels were identified in patients with SFN (Huang et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Sodium channels Nav1.7, Nav1.8, and Nav1.9 are preferentially expressed in peripheral neurons. Gain-of-function mutations of human Nav1.7 and Nav1.8 channels have been associated with SFN (Faber et al 2012a, b;Han et al 2012Han et al , 2014Hoeijmakers et al 2012b;Huang et al 2013). More recently, seven mutations in Nav1.9 channels were identified in patients with SFN (Huang et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Na V 1.7 and Na V 1.8 channels have garnered intense interest because of evidence for their role in human pain disorders [2][3][4][5] , whereas there has previously been no such evidence for Na V 1.9. Our understanding of Na V 1.9 in general has also lagged behind as, unlike Na V 1.7 and Na V 1.8, it has proved difficult to study Na V 1.9 in heterologous expression systems, because it is only expressed at low levels and is difficult to study in isolation in native neurons.…”
mentioning
confidence: 98%
“…Excellent reviews can be found in [6,7 ]. Additional neuropathies have been identified that segregate with mutations on SCN10A and SCN11A, which encode the a-subunits of Na V 1.8 and Na V 1.9, respectively [8][9][10][11][12][13]. Na V 1.7, Na V 1.8 and Na V 1.9 are preferentially distributed in peripheral sensory neurons.…”
Section: Gain-of-function and Loss-of-function Mutationsmentioning
confidence: 98%